Preparation method of solid electrolyte

By mixing lithium sulfide, lithium chloride and phosphorus pentasulfide and sintering and crushing, the problem of low ion conductivity of existing solid electrolytes is solved, and a solid electrolyte with high purity and high ionic conductivity is prepared, which improves battery performance and preparation efficiency.

CN119627187APending Publication Date: 2025-03-14YUXI ENJIE FRONTIER NEW MATERIALS TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411780464.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing solid electrolyte preparation methods lead to low ionic conductivity, affecting battery performance.

Method used

By mixing lithium sulfide, lithium chloride and phosphorus pentasulfide, sintering and then crushing, a solid electrolyte with high purity and high ionic conductivity is prepared.

Benefits of technology

This method can prepare solid electrolytes with high purity and high ionic conductivity, improve preparation efficiency, and prepare products of different particle sizes as needed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627187A_ABST
    Figure CN119627187A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a solid electrolyte, which comprises the following steps: mixing lithium sulfide, lithium chloride and phosphorus pentasulfide to obtain a mixed material; and sintering the mixed material and then crushing to obtain the solid electrolyte. According to the preparation method of the solid electrolyte provided by the invention, the lithium sulfide, the lithium chloride and the phosphorus pentasulfide are mixed and sintered, the preparation efficiency is improved by shortening the time for preparing the mixture, and the solid electrolyte with high purity and high ionic conductivity can be prepared by adopting the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a solid electrolyte. Background Art

[0002] Solid electrolyte batteries have a higher energy density and can store more energy. In addition, solid electrolyte batteries are safer because solid electrolytes are non-flammable, reducing the risk of fire. Therefore, solid electrolytes have significant advantages in battery technology.

[0003] However, the solid electrolyte prepared by the existing method for preparing solid electrolyte has low ion conductivity, which affects the performance of the final battery product. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a solid electrolyte, which can prepare a solid electrolyte with high purity and high ionic conductivity and greatly improve the preparation efficiency.

[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a solid electrolyte, wherein: Mixing lithium sulfide, lithium chloride and phosphorus pentasulfide to obtain a mixed material; The mixed material is sintered and then crushed to obtain the solid electrolyte. The beneficial effect of the preparation method of the solid electrolyte provided by the present invention is that: by mixing lithium sulfide, lithium chloride and phosphorus pentasulfide, sintering the mixture and then crushing it to obtain a solid electrolyte, the preparation method can be used to prepare a solid electrolyte with high purity and high ionic conductivity.

[0006] In some embodiments, sintering the mixed material and then crushing it comprises: The mixed material is subjected to a first sintering to obtain a first sintered material; The first sintered material is first crushed to obtain a solid electrolyte with a particle size of 1-15 μm. The beneficial effect is that the first sintered material is first sintered to obtain a first sintered material, and the first sintered material is first crushed to obtain a solid electrolyte with a particle size of 1-15 μm, so that a variety of products with different particle sizes can be made according to actual needs.

[0007] In some embodiments, sintering the mixed material and then crushing it further comprises: The solid electrolyte with a particle size of 1-15 μm is sand-milled, then dried and sintered for a second time to obtain a second sintered material; The second sintered material is crushed for the second time to obtain the solid electrolyte with a particle size of less than 1 μm. The beneficial effect is that the treatment method can further obtain a solid electrolyte with a particle size of less than 1 μm, and the second sintering can repair the grain boundaries damaged after sanding, thereby improving the performance of the electrolyte.

[0008] In some embodiments, the first crushing includes coarse crushing and fine crushing.

[0009] In some embodiments, the rough breaking comprises: The first sintered material is broken up by using a break-up machine, and then the broken up first sintered material is put into a grinding disc for grinding.

[0010] In some embodiments, the fine crushing includes: placing the first sintered material after coarse crushing into a jet mill for crushing.

[0011] In some embodiments, the step of placing the coarsely crushed first sintered material into a jet mill for crushing comprises: The feeding speed of the air flow mill is adjusted to 3-10 Hz, the crushing pressure of the air flow mill is adjusted to 0.7-0.9 MPa, and the frequency of the classifying wheel in the air flow mill is adjusted to 40-45 Hz.

[0012] In some embodiments, the step of placing the coarsely crushed first sintered material into a jet mill for crushing further comprises: Inert gas is introduced into the jet mill.

[0013] In some embodiments, sand-milling the solid electrolyte having a particle size of 1-15 μm comprises: The solid electrolyte with a particle size of 1-15 μm is placed in a sand mill, and then a solvent is placed in the sand mill. The solvent includes any one or a combination of cyclohexane, n-hexane, anisole, n-heptane, dimethyl carbonate, cyclopentyl methyl ether, xylene and p-xylene.

[0014] In some embodiments, placing the solid electrolyte having a particle size of 1-15 μm into a sand mill comprises: introducing an inert gas into the sand mill; and / or, The second crushing of the second sintering material comprises: The second sintered material is placed in a jet mill for crushing, and then an inert gas is introduced into the jet mill. The beneficial effect is that by introducing an inert gas into the sand mill and the jet mill, the water and oxygen content in the jet mill and the sand mill are removed to ensure that the prepared solid electrolyte has a low water content.

[0015] In some embodiments, the first sintering comprises: Put the mixed material into a crucible, and then put the crucible into a heating furnace for sintering; Passing inert gas into the heating furnace; The second sintering comprises: The sand-ground solid electrolyte is placed in a crucible, and the crucible is then placed in a heating furnace for sintering; Passing inert gas into the heating furnace; The crucible is a sealed crucible. Its beneficial effect is that an inert gas is introduced into the heating furnace to control the water and oxygen content during the sintering process, so as to further control the water content in the solid electrolyte.

[0016] In some embodiments, an inert gas is introduced during the mixing. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A flow chart of a method for preparing a solid electrolyte according to an embodiment of the present invention; Figure 2 The present invention provides a flow chart of a specific preparation method of sintering and then crushing a mixed material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.

[0019] In view of the problems existing in the prior art, an embodiment of the present invention provides a method for preparing a solid electrolyte. Figure 1 The preparation method shown comprises: S100: mixing lithium sulfide, lithium chloride and phosphorus pentasulfide to obtain a mixed material.

[0020] In this step, a high-speed mixer can be used to mix lithium sulfide, lithium chloride and phosphorus pentasulfide. Specifically, the line speed of the high-speed mixer can be adjusted to 20-50 m / s, and the mixing time of the high-speed mixer can be controlled to be 30-60 min. By using a high-speed mixer to mix lithium sulfide, lithium chloride and phosphorus pentasulfide, the time required for mixing can be reduced and the uniformity of the mixing can be improved.

[0021] In addition, when the high-speed mixer is mixing materials, an inert gas, such as nitrogen, can be introduced into the high-speed mixer to remove the water and oxygen content in the high-speed mixer and the mixed materials.

[0022] S200: sintering the mixed material and then crushing it to obtain the solid electrolyte.

[0023] This step may specifically include the following steps: S201: sintering the mixed material for the first time to obtain a first sintered material.

[0024] In this step, the mixed material can be placed in a crucible, and then the crucible is placed in a heating furnace, and then the temperature of the heating furnace is adjusted to 450-600° C., and the mixed material is sintered for 5-9 hours to obtain a first sintered material.

[0025] It should be noted that the crucible can be a closed crucible. When a heating furnace is used to perform the first sintering of the mixed material in the crucible, nitrogen can be introduced into the heating furnace to control the water and oxygen content during the sintering process, and the water and oxygen content in the heating furnace is controlled to be below 10 ppm, thereby effectively controlling the moisture content of the first sintered material during the preparation process.

[0026] S202: performing a first crushing on the first sintered material to obtain a solid electrolyte with a particle size of 1-15 μm.

[0027] In this step, the first crushing includes coarse crushing and fine crushing. Specifically, the first sintered material is preliminarily subjected to coarse crushing, and then the coarsely crushed first sintered material is placed in an air flow mill for fine crushing. By adjusting the parameters of the air flow mill, the solid electrolyte with a particle size of 1-15 μm can be obtained. For example, the feeding speed of the air flow mill is adjusted to 3-10 Hz, the crushing pressure of the air flow mill is adjusted to 0.7-0.9 MPa, and the frequency of the classifying wheel in the air flow mill is adjusted to 40-45 Hz, and finally a solid electrolyte with a particle size of 1-3 μm or 10-15 μm can be obtained.

[0028] The method for roughly crushing the first sintered material can be implemented by using a disintegrator and a grinding disc. Specifically, the first sintered material is firstly disintegrated by a disintegrator, and then the disintegrated first sintered material is put into the grinding disc through the hopper of the rotary mill for grinding, so as to control the particle size of the first sintered material to be 1-3 mm, and finally the first sintered material after rough crushing is obtained.

[0029] In addition, in order to further effectively control the water and oxygen content in the solid electrolyte, when the first sintered material after coarse crushing is placed in a gas flow mill for crushing, an inert gas needs to be introduced into the gas flow mill to replace and remove the water and oxygen content in the gas flow mill and the first sintered material, and the water and oxygen content in the gas flow mill is controlled below 10ppm.

[0030] S203: sand-grinding the solid electrolyte with a particle size of 1-15 μm, and then drying and performing a second sintering to obtain a second sintered material.

[0031] In this step, a sand mill can be used to sand grind the solid electrolyte with a particle size of 1-15 μm, specifically by adjusting the rotation speed of the sand mill to 1000-3000 rpm / min, adjusting the air pressure in the sand mill to 0.1-0.5 MPa, and adjusting the solid content in the sand mill to 10%-50%. Then, a solvent is put into the sand mill, and the solvent includes any one or a combination of cyclohexane, n-hexane, anisole, n-heptane, dimethyl carbonate, cyclopentyl methyl ether, xylene and p-xylene.

[0032] In the process of sand milling the solid electrolyte, an inert gas can be introduced into the sand mill to remove the water and oxygen content in the sand mill and the solid electrolyte, and the water content in the sand mill is controlled below 10 ppm and the oxygen content is controlled below 10 ppm.

[0033] Next, the sand-milled solid electrolyte is placed in a dryer, and the temperature of the dryer is controlled at 110-200° C. for a drying time of 3-24 hours to reduce the moisture content in the sand-milled solid electrolyte and volatilize the solvent.

[0034] Finally, the dried solid electrolyte can be placed in a crucible, and then the crucible can be placed in a heating furnace. The temperature of the heating furnace is then adjusted to 200-400° C. and heated for 1-10 hours to obtain a second sintering material.

[0035] It should be noted that the crucible can be a closed crucible. When a heating furnace is used to perform the first sintering of the solid electrolyte placed in the crucible after drying, nitrogen can be introduced into the heating furnace to control the water and oxygen content during the sintering process, and the water and oxygen content in the heating furnace is controlled to be below 10 ppm, thereby effectively controlling the moisture content of the second sintering material during the preparation process.

[0036] S204: crushing the second sintered material for a second time to obtain the solid electrolyte with a particle size less than 1 μm.

[0037] In this step, the second crushing refers to placing the second sintered material into a gas flow mill for crushing again to obtain the solid electrolyte with a particle size less than 1 μm. At the same time, an inert gas needs to be introduced into the gas flow mill to replace and remove the water and oxygen content in the gas flow mill and the solid electrolyte, and the water content in the gas flow mill is controlled below 10 ppm, and the oxygen content is controlled below 10 ppm.

[0038] In this embodiment, a solid electrolyte is prepared by adopting the above-mentioned preparation method, which has the characteristics of high purity and high ionic conductivity, and the moisture content of the prepared solid electrolyte can be efficiently controlled within the range of 40-500ppm, and the residual solvent is within 50ppm. In addition, solid electrolytes of different particle sizes can be prepared as needed, which greatly improves the overall efficiency of the preparation.

[0039] Embodiment 1 The present invention provides a method for preparing a solid electrolyte, and the preparation method specifically comprises the following steps: Step 1: lithium sulfide, lithium chloride and phosphorus pentasulfide are placed in a high-speed mixer in a certain proportion and mixed to obtain a mixture. The line speed of the high-speed mixer is set at 35 m / s, the mixing time is 45 min, and the water content and oxygen content in the high-speed mixer are controlled to be below 10 ppm and below 10 ppm, respectively. Step 2: Put the mixed material into a crucible, and then put the crucible into a heating furnace for the first sintering to obtain the first sintered material. The temperature in the heating furnace is set at 550°C, the heating time is 8 hours, and the water content in the heating furnace is controlled to be below 10ppm and the oxygen content is controlled to be below 10ppm.

[0040] Step 3: Pre-break up the first sintered material by a break-up machine, and then grind the broken up first sintered material into a grinding disc to obtain a first sintered material with a particle size of 1-3 mm. Control the water content in the break-up machine and the grinding disc to be below 10 ppm, and the oxygen content to be below 10 ppm.

[0041] Step 4: Put the first sintered material with a particle size of 1-3mm into an air flow mill for crushing to obtain a solid electrolyte with a particle size of 1-15μm. Among them, the particle size of the solid electrolyte can be further controlled by adjusting the parameters of the air flow mill, and the water content in the air flow mill is controlled to be below 10ppm and the oxygen content is controlled to be below 10ppm. For example, the feeding speed of the air flow mill is adjusted to 3HZ, the crushing pressure of the air flow mill is adjusted to 0.8MPa, and the frequency of the classifying wheel in the air flow mill is adjusted to 40HZ to obtain a solid electrolyte with a particle size of 1-3μm. For another example, the feeding speed of the air flow mill is adjusted to 8HZ, the crushing pressure of the air flow mill is adjusted to 0.7MPa, and the frequency of the classifying wheel in the air flow mill is adjusted to 43HZ to obtain a solid electrolyte with a particle size of 10-15μm.

[0042] Embodiment 2 The present invention provides a method for preparing a solid electrolyte, which differs from the first embodiment in that after preparing a solid electrolyte with a particle size of 10-15 μm by adjusting the parameters of the airflow mill, the solid electrolyte with a particle size of 10-15 μm is further processed to obtain a solid electrolyte with a particle size of less than 1 μm, wherein the specific preparation method is as follows: (1) Put a solid electrolyte with a particle size of 10-15 μm into a sand mill for sand grinding. The speed of the sand mill is adjusted to 2000 rpm / min, the air pressure in the sand mill is adjusted to 0.3 Mpa, the solid content in the sand mill is adjusted to 25%, and the water content in the sand mill is controlled to be below 10 ppm and the oxygen content is controlled to be below 10 ppm. In addition, during the sand grinding process in the sand mill, a solvent is put into the sand mill, and the solvent includes any one or a combination of cyclohexane, n-hexane, anisole, n-heptane, dimethyl carbonate, cyclopentyl methyl ether, xylene and p-xylene.

[0043] (2) The sand-milled solid electrolyte is placed in a dryer for drying. The temperature of the dryer is set at 190°C, the drying time is set at 20 hours, and the water content and oxygen content in the dryer are controlled to be below 10 ppm and below 10 ppm.

[0044] (3) The dried solid electrolyte is placed in a crucible, and then the crucible is placed in a heating furnace for a second sintering to obtain a second sintered material. During the second sintering, the temperature in the heating furnace is set at 250°C and the heating time is 5 hours. The second sintering can repair the grain boundaries damaged after sanding and improve the performance of the electrolyte. The water content in the heating furnace is controlled to be below 10 ppm and the oxygen content is controlled to be below 10 ppm.

[0045] (4) The second sintered material is placed in an air flow mill for crushing to obtain the solid electrolyte with a particle size of less than 1 μm. The feeding speed of the air flow mill is adjusted to 4 Hz, the crushing pressure of the air flow mill is adjusted to 0.85 MPa, the frequency of the classifying wheel in the air flow mill is adjusted to 45 Hz, the solid electrolyte with a particle size of less than 1 μm is obtained, and the water content in the air flow mill is controlled to be less than 10 ppm and the oxygen content is controlled to be less than 10 ppm.

[0046] Embodiment 3 The present invention provides a method for preparing a solid electrolyte, which differs from Embodiment 1 or Embodiment 2 in that, in the present embodiment, the crucible is a closed crucible, and when the mixed material or the dried solid electrolyte in the closed crucible is sintered in a heating furnace, nitrogen needs to be continuously introduced into the heating furnace to control the water and oxygen content during the sintering process.

[0047] Furthermore, in this embodiment, when the material is processed by a jet mill, a high-speed mixer, or a sand mill, nitrogen needs to be introduced into the jet mill, the high-speed mixer, or the sand mill to remove the water and oxygen content in the corresponding equipment.

[0048] Comparative Example 1 The preparation method is the same as that in Example 1, except that: in step 1, the water content in the high mixer is controlled to be 168ppm and the oxygen content is controlled to be 300ppm; in step 2, the water content in the heating furnace is controlled to be 189ppm and the oxygen content is controlled to be 300ppm; in step 3, the water content in the pulverizer and the grinding disc is controlled to be 13687ppm and the oxygen content is controlled to be 10000ppm; in step 4, the water content in the air flow mill is controlled to be 368ppm and the oxygen content is controlled to be 800ppm. The particle size of the solid electrolytes of Examples 1-3 and Comparative Example 1 is measured by a laser particle size tester, and the ionic conductivity is measured by an AC impedance meter, and the test results are shown in Table 1.

[0049] Table 1

[0050] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a solid electrolyte, characterized in that: The preparation method: Mixing lithium sulfide, lithium chloride and phosphorus pentasulfide to obtain a mixed material; The mixed material is sintered and then crushed to obtain the solid electrolyte.

2. The method for preparing a solid electrolyte according to claim 1, characterized in that: The mixed material is sintered and then crushed, comprising: The mixed material is subjected to a first sintering to obtain a first sintered material; The first sintered material is crushed for the first time to obtain a solid electrolyte with a particle size of 1-15 μm.

3. The method for preparing a solid electrolyte according to claim 2, characterized in that: The mixed material is sintered and then crushed, and the process further comprises: The solid electrolyte with a particle size of 1-15 μm is sand-milled, then dried and sintered for a second time to obtain a second sintered material; The second sintered material is crushed for the second time to obtain the solid electrolyte with a particle size less than 1 μm.

4. The method for preparing a solid electrolyte according to claim 2, characterized in that: The first crushing includes coarse crushing and fine crushing.

5. The method for preparing a solid electrolyte according to claim 4, characterized in that: The rough crushing includes: The first sintered material is broken up by using a break-up machine, and then the broken up first sintered material is put into a grinding disc for grinding.

6. The method for preparing a solid electrolyte according to claim 4, characterized in that: The fine crushing includes: putting the first sintered material after coarse crushing into a jet mill for crushing.

7. The method for preparing a solid electrolyte according to claim 6, characterized in that: The step of placing the coarsely crushed first sintered material into a jet mill for crushing comprises: The feeding speed of the air flow mill is adjusted to 3-10 Hz, the crushing pressure of the air flow mill is adjusted to 0.7-0.9 MPa, and the frequency of the classifying wheel in the air flow mill is adjusted to 40-45 Hz.

8. The method for preparing a solid electrolyte according to claim 6, characterized in that: The step of placing the coarsely crushed first sintered material into a jet mill for crushing further comprises: An inert gas is introduced into the air flow pulverizer.

9. The method for preparing a solid electrolyte according to claim 3, characterized in that: The sand grinding of the solid electrolyte having a particle size of 1-15 μm comprises: The solid electrolyte with a particle size of 1-15 μm is placed in a sand mill, and then a solvent is placed in the sand mill. The solvent includes any one or a combination of cyclohexane, n-hexane, anisole, n-heptane, dimethyl carbonate, cyclopentyl methyl ether, xylene and p-xylene.

10. The method for preparing a solid electrolyte according to claim 9, characterized in that: The step of placing the solid electrolyte having a particle size of 1-15 μm into a sand mill comprises: introducing an inert gas into the sand mill; and / or, The second crushing of the second sintering material comprises: The second sintered material is placed in a jet mill for crushing, and then an inert gas is introduced into the jet mill.

11. The method for preparing a solid electrolyte according to claim 3, characterized in that: The first sintering comprises: Put the mixed material into a crucible, and then put the crucible into a heating furnace for sintering; Passing inert gas into the heating furnace; The second sintering comprises: The sand-ground solid electrolyte is placed in a crucible, and the crucible is then placed in a heating furnace for sintering; Passing inert gas into the heating furnace; Wherein, the crucible is a closed crucible.

12. The method for preparing a solid electrolyte according to claim 1, characterized in that: During the mixing, an inert gas is introduced.

Citation Information

Patent Citations

  • Preparation method and application of Li6PS5Cl sulfide solid electrolyte

    CN117525555A

  • Sulfide and preparation method thereof, solid electrolyte, all-solid-state battery and electric equipment

    CN117594868A

  • Preparation method of solid electrolyte, all-solid-state battery and preparation method of all-solid-state battery

    CN117658178A

  • Sulfide electrolyte and preparation method thereof

    CN118117152A

  • Preparation method of sulfide solid electrolyte based on vibration ball milling method

    CN118472404A